An overabundance of phase 0 introns immediately after the start codon in eukaryotic genes - Wernersson Rasmus; Nielsen Henrik (BMC Genomics, 2006)
Abstract Background A knowledge of the positions of introns in eukaryotic genes is important for understanding the evolution of introns. Despite this, there has been relatively little focus on the distribution of intron positions in genes. Results In proteins with signal peptides, there is an overabundance of phase 1 introns around the region of the signal peptide cleavage site. This has been described before. But in proteins without signal peptides, a novel phenomenon is observed: There is a sharp peak of phase 0 intron positions immediately following the start codon, i.e. between codons 1 and 2. This effect is seen in a wide range of eukaryotes: Vertebrates, arthropods, fungi, and flowering plants. Proteins carrying this start codon intron are found to comprise a special class of relatively short, lysine-rich and conserved proteins with an overrepresentation of ribosomal proteins. In addition, there is a peak of phase 0 introns at position 5 in Drosophila genes with signal peptides, predominantly representing cuticle proteins. Conclusion There is an overabundance of phase 0 introns immediately after the start codon in eukaryotic genes, which has been described before only for human ribosomal proteins. We give a detailed description of these start codon introns and the proteins that contain them.